(TMT)n clusters as dilute debris‐free tin source for generation of multiply charged tin ions of relevance in extreme ultraviolet (EUV) lithography, under intense laser irradiation. (7th June 2018) - Sharma, Pramod; Das, Soumitra; Vatsa, Rajesh K.
Abstract : Rationale: Multiply charged tin ions ([Sn] 8+ to [Sn] 13+ ) are considered as ideal‐emitters at extreme ultraviolet (EUV) wavelength ~13.5 nm, pertinent to the fabrication of advanced micro‐electronic devices. Solid tin targets have been widely explored for the generation of these ions, but debris generation has restricted their utilization. Tin‐containing molecular clusters have the potential to act as dilute and debris‐free sources for the generation of tin ions, as investigated in the present study. Methods: Efficient coupling of laser energy with clusters has been utilized for the generation of multiply charged tin ions. The ions generated have been characterized using time‐of‐flight mass spectrometry. By varying experimental parameters, the yield of multiply charged tin ions has been manipulated, for tetramethyltin (TMT) clusters. In addition, the energetic electrons and photons liberated upon laser‐cluster interaction have been probed utilizing an in‐house developed retarding field analyzer. Results: Interaction of TMT clusters with 1064 nm picosecond laser pulses of intensity ~10 13  W/cm 2 leads to the generation of multiply charged tin ions (up to [Sn] 14+ ) and carbon ions (up to [C] 4+ ). Efficient laser‐cluster interaction is evident from the generation of multiply charged tin ions with ionization energy ~282 eV ([Sn] 14+ ). By varying the experimental conditions, the distribution of multiply charged tin ions can be influenced to obtain significant relative ion yields of multiply charged tin ions from [Sn] 8+ to [Sn] 13+ . Conclusions: Tetramethyltin clusters have the potential to act as dilute and debris‐free sources for EUV lithographic applications, in contrast to bulk tin targets. The inherent properties of clusters, such as higher local density and the pulsed nature of the cluster source, are appropriate for EUV lithographic applications.